CineCulture screens 'Scarlet Empress', Jan. 25 - Uribes, Tom::::::::: (2013)
Fresno State's CineCulture spring film series begins at 5:30 p.m. Friday, Jan. 25, at the Leon S. and Pete P. Peters Educational Center in the Student Recreation Center (Woodrow and Shaw avenues) with a screening of 'The Scarlet Empress.'